Butyrate-induced IL-22 expression in fish macrophages contributes to bacterial clearance. Issue 133 (February 2023) - Zhang, Jinjin; Wang, Wentao; Liang, Shufei; Shao, Rui; Shi, Wenkai; Gudmundsson, Gudmundur H.; Bergman, Peter; Ai, Qinghui; Mai, Kangsen; Wan, Min
Abstract: IL-22 has been characterized as a critical cytokine in maintaining barrier integrity and host immunity. So far, it has been known that IL-22 is mainly produced by lymphoid lineage cells. In the present study, we have thoroughly investigated butyrate-induced production and function of IL-22 in fish macrophages. Our results demonstrated that short-chain fatty acids (SCFAs), major microbiota-derived metabolites, promoted the expression of IL-22 in head kidney macrophages (HKMs) of turbot ( Scophthalmus maximus L.). Interestingly, butyrate-mediated intracellular bacterial killing in HKMs diminished when IL-22 expression was interfered. Furthermore, the turbot fed the diet containing sodium butyrate (NaB) exhibited significantly lower mortality after bacterial infection, compared to the fish fed a basal diet. At the meantime, a higher level of IL-22 expression and bactericidal activity was detected in HKMs from the turbot fed NaB-supplemented diet. In addition, NaB treatment promoted the expression of antimicrobial peptides (AMPs) β-defensins in zebrafish ( Danio rerio ). However, butyrate-induced expression of AMPs was reduced in IL-22 mutant zebrafish compared to wild-type (WT) fish. Meanwhile, NaB treatment was incapable to protect IL-22 mutant fish from bacterial infection as it did in WT zebrafish. Importantly, our results demonstrated that IL-22 expression was remarkably suppressed in macrophage-depleted zebrafish, indicating that macrophage might be a cell source of IL-22 production in vivo . In conclusion, all these findings collectively revealed that SCFAs regulated the production and function of IL-22 in fish macrophages, which facilitated host resistance to bacterial invasion. Highlights: Butyrate induces IL-22 production in fish macrophages. HIF-1α is involved in butyrate-induced IL-22 expression in head kidney macrophages. IL-22 promotes the secretion of antibacterial components in macrophages to eliminate pathogens. Fish macrophages could be a cell source for IL-22 in vivo.